Prevalence and Risk Factors of Sexually Transmitted Infections in a Tertiary Hospital in Surakarta, Indonesia - Lidjaja, Lifesia Natali; Ammarilis Murastami; Endra Yustin Ellistasari; Ivani; Vrenda Alia (HM Publisher, 2025)
Background: Sexually transmitted infections (STIs) remain a significant public health concern globally, with millions of new cases occurring annually. Understanding the prevalence and risk factors associated with STIs is crucial for effective prevention and control programs. This study aimed to investigate the prevalence and risk factors of STIs among patients attending the Dermatology and Venereology Outpatient Clinic of Dr. Moewardi General Hospital, a tertiary hospital in Surakarta, Indonesia. Methods: A retrospective descriptive study was conducted using secondary data from medical records of patients diagnosed with STIs between January 2020 and December 2023. Data collected included sociodemographic characteristics, sexual behaviors, clinical diagnoses, and HIV status. Descriptive statistics and chi-square analysis were used to analyze the data. Results: A total of 249 patients were diagnosed with STIs during the study period. The most common STI was condyloma acuminata (51%), followed by male genital discharge (18.1%), female vaginal discharge (16%), other STIs (10.9%), and genital ulcers (4%). The majority of patients were male (62.2%), aged 25-44 years (49.1%), had a high school education (49.5%), and reported heterosexual orientation (67.1%). Multiple sexual partners were reported by 62.7% of the participants, and 36.1% were HIV positive. The correlation analysis reveals that various sociodemographic, behavioral, and health-related factors are associated with different STIs. Conclusion: Condyloma acuminata was the most prevalent STI among patients attending the Dermatology and Venereology Outpatient Clinic of Dr. Moewardi General Hospital. The correlation analysis reveals that various sociodemographic, behavioral, and health-related factors are associated with different STIs. Understanding these correlations can help healthcare providers identify individuals at higher risk for specific STIs and implement targeted prevention and intervention strategies. Targeted interventions focusing on these high-risk groups are needed to reduce the burden of STIs in Surakarta, Indonesia.